Postural stability, clicker reaction time and bow draw force predict performance in elite recurve archery - Spratford, W.; Campbell, R. (European Journal of Sport Science, 2017)
Recurve archery is an Olympic sport that requires extreme precision, upper body strength and endurance. The purpose of this research was to quantify how postural stability variables both pre- and post-arrow release, draw force, flight time, arrow length and clicker reaction time, collectively, impacted on the performance or scoring outcomes in elite recurve archery athletes. Thirty-nine elite-level recurve archers (23 male and 16 female; mean age = 24.7 ± 7.3 years) from four different countries volunteered to participate in this study prior to competing at a World Cup event. An AMTI force platform (1000Hz) was used to obtain centre of pressure (COP) measurements 1s prior to arrow release and 0.5s post-arrow release. High-speed footage (200Hz) allowed for calculation of arrow flight time and score. Results identified clicker reaction time, draw force and maximum sway speed as the variables that best predicted shot performance. Specifically, reduced clicker reaction time, greater bow draw force and reduced postural sway speed post-arrow release were predictors of higher scoring shots. It is suggested that future research should focus on investigating shoulder muscle tremors at full draw in relation to clicker reaction time, and the effect of upper body strength interventions (specifically targeting the musculature around the shoulder girdle) on performance in recurve archers.